2023
DOI: 10.6023/a22110462
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Thermal Failure Mechanism and Ternary Blending to Improve Thermal Stability of Organic Solar Cells

Abstract: As an emerging high-efficiency solar cell, organic solar cells (OSCs) have been developed rapidly in recent years. The power conversion efficiency (PCE) of OSCs has reached more than 19%, which is the dawn of commercial application. However, the stability of OSCs is not yet satisfied, especially high processing and operation temperature may be applied to the cells, which requires a high thermal stability of the cells. The ternary strategy, where a third component is introduced into the photoactive layer of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 128 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…Extracellular enzymes from microorganisms generally play an essential role in inducing and accelerating spoilage processes, including texture softening and TVB-N production [29] . Pseudomonas and Shewanella were reported that they could hydrolyze triglycerides into fatty acids and glycerol by lipases and degrade muscle and connective tissue by proteases, which could cause stronger spoilage and contribute to growth of bacteria when the nutrients on the surface of meat were completely used [8,[30][31] . Some Pseudomonas species can even produce proteases and lipases even under low temperatures [32][33] .…”
Section: Assessment Of Spoilage Ability In Situmentioning
confidence: 99%
“…Extracellular enzymes from microorganisms generally play an essential role in inducing and accelerating spoilage processes, including texture softening and TVB-N production [29] . Pseudomonas and Shewanella were reported that they could hydrolyze triglycerides into fatty acids and glycerol by lipases and degrade muscle and connective tissue by proteases, which could cause stronger spoilage and contribute to growth of bacteria when the nutrients on the surface of meat were completely used [8,[30][31] . Some Pseudomonas species can even produce proteases and lipases even under low temperatures [32][33] .…”
Section: Assessment Of Spoilage Ability In Situmentioning
confidence: 99%